Neuronal modulation of brown adipose activity through perturbation of white adipocyte lipogenesis - Adilson Guilherme; David J. Pedersen; Felipe Henriques; Alexander H. Bedard; Elizabeth Henchey; Mark Kelly; Donald A. Morgan; Kamal Rahmouni; Michael P. Czech (Elsevier, 2018)
Objective: Crosstalk between adipocytes and local neurons may be an important regulatory mechanism to control energy homeostasis. We previously reported that perturbation of adipocyte de novo lipogenesis (DNL) by deletion of fatty acid synthase (FASN) expands sympathetic neurons within white adipose tissue (WAT) and stimulates the appearance of "beige" adipocytes. Here we tested whether WAT DNL activity can also influence neuronal regulation and thermogenesis in brown adipose tissue (BAT). Methods and results: Induced deletion of FASN in all adipocytes in mature mice (iAdFASNKO) enhanced sympathetic innervation and neuronal activity as well as UCP1 expression in both WAT and BAT. This increased sympathetic innervation could be observed at both 22 °C and 30 °C, indicating it is not a response to heat loss but rather adipocyte signaling. In contrast, selective ablation of FASN in brown adipocytes of mice (iUCP1FASNKO) failed to modulate sympathetic innervation and the thermogenic program in BAT. Surprisingly, DNL in brown adipocytes was also dispensable in maintaining euthermia when UCP1FASNKO mice were cold-exposed. Conclusion: These results indicate that DNL in white adipocytes influences long distance signaling to BAT, which can modify BAT sympathetic innervation and expression of genes involved in thermogenesis. Keywords: Adipocytes, Lipogenesis, Brown adipose tissue, Thermogenesis, Sensory nerve, Sympathetic nerve, SNS outflow